2014
DOI: 10.1055/s-0034-1382035
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Status is Different in Relationship to Insulin Resistance in Severely Obese People and Changes after Bariatric Surgery or Diet-induced Weight Loss

Abstract: NK cells are significantly increased in IR severely obese people in respect to IS, suggesting a slightly different immune status in these patients with a probable dietary relationship. Weight loss could reverse this increase either after VLCD or after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…However, the effect of EGCG on insulin resistance and its mechanism in treating NAFLD has rarely been discussed. In our study, EGCG allevi- (Table 1), as previously shown wherein weight loss induced by diet control, exercise, pharmacotherapy and bariatric surgery improves insulin resis tance [26,27] . However, more importantly, our study confirmed that an EGCG-induced increase in insulin clearance may contribute to the improvement of insulin resistance in NAFLD mice ( Figure 6).…”
Section: Discussionsupporting
confidence: 74%
“…However, the effect of EGCG on insulin resistance and its mechanism in treating NAFLD has rarely been discussed. In our study, EGCG allevi- (Table 1), as previously shown wherein weight loss induced by diet control, exercise, pharmacotherapy and bariatric surgery improves insulin resis tance [26,27] . However, more importantly, our study confirmed that an EGCG-induced increase in insulin clearance may contribute to the improvement of insulin resistance in NAFLD mice ( Figure 6).…”
Section: Discussionsupporting
confidence: 74%
“…Aside from morbid obesity, total NK cell counts have been reported in the peripheral blood of donors with insulin resistance and have declined following weight reduction, suggesting an immune metabolic disorder. Because CD56 bright NK cells were less numerous (data not shown), our results focused on circulating cytotoxic CD56 dim cells.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of a clear cut-off for defining IR in children and adolescents is also a problem [6]. Moreover the results of the recently published studies point to significant differences between pediatric and adult mechanisms of the IR development, the close correlation between IR and immune status and thyroid function [8][9][10]. A novel insight into these problems is possible since the analysis of the expression of central obesity (CO) and Type 2 Diabetes Mellitus genes has became achievable [11][12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%